Analysis of the Work Environment in Efforts to Improve the Quality and Effectiveness of Human Resources at PT ATI Talenta Sembilan South Jakarta - Indra Januar Rukmana; Shela Indah Savitri; Syawaludin Syawaludin (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study aims to analyze the role of the work environment in improving the quality and effectiveness of human resources at . The study employed a qualitative descriptive approach to understand workplace conditions, employee perceptions, and organizational efforts in creating a conducive work environment. Data were collected through observations, interviews, and documentation involving company management and employees. The findings indicate that both physical and non-physical work environments significantly influence employee comfort, productivity, communication, and organizational effectiveness. Supportive workplace facilities, positive interpersonal relationships, and continuous employee development programs contribute positively to improving human resource quality within the organization. However, several challenges were identified, particularly related to technological infrastructure limitations, workload management, and communication effectiveness. The SWOT analysis further revealed that the company is positioned in a favorable strategic condition, indicating strong organizational potential for growth and development through the optimization of workplace quality and employee competency enhancement. The study concludes that organizations operating in technology-based industries must continuously improve workplace conditions, strengthen organizational communication, and invest in employee development programs in order to maintain long-term organizational effectiveness and competitiveness